Literature review of recent, practical - oriented computer networks papers - Islam, Hasibul; Sameer, Hassan; Farooq, Irtiza Ahmad (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2009.